Spiritualitas dan Pemulihan untuk Meningkatkan Harga Diri Pecandu Narkoba: Tarekat Al-Qadiria An-Naqsyabandia Sebagai Model - Jamal, Fauzun; Hasanah, Nur (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2024)
This research aims to reveal the spiritual process adopted by the Thareqa Qadiriya Naqshbandi of treating drug addicts and improving their condition and self-esteem. An in-depth study of young drug addicts confirmed that they suffered from poor self-esteem. Suryalaya (pesantren/Islamic boarding school) is among the institutions that take care of this social problem at the forefront, it has treated young drug addicts with its own spiritual exercise. The field research explain on recovery by spiritual exercise, especially to improve their self-esteem, the researcher followed the progress of the healers' conditions for four consecutive months -they were randomly selected samples from the real community subject to research- and also conducted an in-depth interview to collect information related to the research until reached the research results, pointed to the possibility of activating spiritual teachings in addressing modern social problems.